Hubungan Kelengkapan Imunisasi Dasar dengan Kejadian Stunting pada Balita Usia 24-36 Bulan di Wilayah Kerja Puskesmas Lima Puluh Tahun 2024 - Yessi Rahayu; Yulnefia Yulnefia; Irgi Rahmaddani (Pusat riset dan Inovasi Nasional, 2025)
Stunting is a chronic nutritional problem in toddlers caused by a lack of nutritional intake for a long time so that the child becomes too short for his age. Based on the results of the Indonesian Nutrition Standards Survey (SSGI) in 2022 in Riau province, it reached 17.0%. The prevalence rate of stunting in Pekanbaru reached around 16.8% in 2022. According to the Health Office in 2022, Lima Puluh Health Center recorded the highest prevalence of stunting at 4.47% or 60 cases. One of the risk factors that contributes to stunting is the low coverage of complete basic immunization, which can prevent infectious diseases that can interfere with children's growth and development. However, the lack of public knowledge and awareness of the importance of complete basic immunization increases the risk of infection. The long-term impacts of stunting include cognitive impairment, developmental delays, and low productivity in the future. Knowing the relationship between the completeness of basic immunization and the incidence of stunting in toddlers aged 24-36 months in the Lima Puluh Health Center work area, Pekanbaru City. to determine the relationship between the completeness of basic immunization and the incidence of stunting in toddlers aged 24-36 months in the Lima Puluh Health Center work area, Pekanbaru City. From the results of data analysis, a relationship has been found between the completeness of immunization and the incidence of stunting in toddlers aged 24-36 months in the Lima Puluh Health Center work area (p-value = 0.03; OR of 11.66; (95% CI = 1.22-110.95). Completeness of basic immunization is related and is a risk factor for stunting in toddlers aged 24-36 months in the Limapuluh Health Center work area.